IEO Annual Report, 2008. (Independent Evaluation Office Reports; Independent Evaluation Office Reports, 2008)
This fifth Annual Report describes the activities of the Independent Evaluation Office (IEO) during the year to April 30, 2008. This period saw the completion of two evaluations, "Structural Conditionality in IMF-Supported Programs" smf "Governance of the IMF".